The midterm outcomes of ankle Dias-Tachdjian pronation-eversion external rotation physeal fracture in children treated by open reduction internal fixation with one-stage medial-lateral combined incision. Issue 5 (September 2021) - Xiang, Feng; Li, Bo; Xiao, Sheng; Liu, Hong; Wen, Jie; Li, Xin; Fang, Ke; Zeng, Ming; Tang, Zhongwen; Cao, Shu; Lee, Bo; Li, Fanling
Abstract : The objective of this study was to report the midterm outcomes and complications of ankle Dias-Tachdjian pronation-eversion external rotation (PEER) physeal fracture in children treated by ORIF with combined medial and lateral incision. A total of 21 children with ankle Dias-Tachdjian PEER physeal fracture underwent open reduction internal fixation treatment with combined medial and lateral incision between January 2015 and October 2017. The lateral distal tibia angle (LDTA) was measured to evaluate angular deformity and the X-rays were taken to evaluate the premature physeal arrest. All patients were followed up for an average time of 20.1 months (ranging from 17 to 25 months). Bone healing was achieved in all cases. American Orthopedic Foot and Ankle Society-Ankle and Hindfoot (AOFAS-AH) score of the patients improved from median 31 (11, 38) preoperation to median 68 (63, 73) postoperation to median score 91 (87, 96) at last follow-up. LDTA of the patients improved from 70.5 ± 4.9 preoperation to 90.0 ± 1.2 postoperation, to measure 90.6 ± 3.7 at last follow-up. The differences were statistically significant ( P  < 0.05). There is no premature physeal closure, ankle deformity in 19 cases. They could normally exercise and take part in normal sport activities. The remaining two cases had physeal bone bridge and premature physeal closure but could still carry on daily activities and thus were categorized as good. ORIF with one-stage medial-lateral combined incision for ankle Dias-Tachdjian PEER physeal fracture can decrease the rate of premature physeal closure and should be a treatment choice.